Soy isoflavone intake inhibits bone resorption and stimulates bone formation in menopausal women: meta-analysis of randomized controlled trials - Ma, D.F; Qin, L.Q; Wang, P.Y; Katoh, R (European journal of clinical nutrition, 2008)
Objective: To clarify the effects of isoflavone intake on bone resorption and bone formation. Methods: We identified randomized controlled trials related to urinary deoxypyridinoline (Dpyr, a bone resorption marker) and serum bone-specific alkaline phosphatase (BAP, a bone formation marker) listed on MEDLINE (January 1966-April 2006), the Cochrane Controlled Trials Register, EMBASE (1985-January 2006), Science Citation Index and PUBMED (updated till April 2006). Results: Nine studies with a total of 432 subjects were selected for meta-analysis. The urinary Dpyr concentration in subjects who consumed isoflavones decreased significantly by -2.08 nmol/mmol (95% confidence interval (CI): -3.82 to -0.34 nmol/mmol) in comparison with that in subjects who did not consume isoflavones. Isoflavone intake vs placebo intake significantly increased serum BAP by 1.48 microgram/l (95% CI: 0.22-2.75 microgram/l). Decreases in the urinary Dpyr concentration with isoflavone intake of <90 mg/day and with treatment lasting less than 12 weeks were -2.34 nmol/mmol (95% CI: -4.46 to -0.22 nmol/mmol) and -2.03 nmol/mmol (95% CI: -3.20 to -0.85 nmol/mmol), respectively. Conclusions: Isoflavone intervention significantly inhibits bone resorption and stimulates bone formation. These favorable effects occur even if <90 mg/day of isoflavones are consumed or the intervention lasts less than 12 weeks.